Pengaruh Pembiayaan Kredit Usaha Rakyat (KUR) Terhadap Perkembangan Usaha Mikro Kecil dan Menengah di PT Bank BSI KCP Nagan Raya 2 - Fitriyani, Nur; Fatmayanti, Fatmayanti (Journal of Economics, Bussiness and Management Issues, 2023)
People's Business Credit (KUR) can provide capital and encourage the development of community businesses which ultimately affects the income earned. For this reason, it is very important to develop KUR to reduce poverty levels and increase the contribution of MSMEs to the local economy. This research aims to see how KUR financing influences the development of MSMEs, and how this can help overcome the problems of unemployment and poverty and provide benefits to the community in Nagan Raya Simpang Peut. This research uses quantitative methods with a sample of 30 people from People's Business Credit (KUR) borrower customers at PT Bank BSI KCP Nagan Raya 2. The data collection technique uses a questionnaire, where after the data is collected it will be tested for validity and reliability to ensure validity and reliability. reliability of data obtained from respondents. Then afterwards it will be analyzed using the Likert scale technique. The findings obtained are that through KUR loans, MSME businesses can grow and develop because KUR can provide opportunities for MSME players to increase capital and expand operational scale so that they can increase production and product marketing. KUR has a positive impact, namely that it can increase income, welfare and provide new job opportunities.